24.5k views
4 votes

y = (1)/(2) + (w)/(3)
express w in terms of y ​

User Intl
by
5.2k points

1 Answer

3 votes

Answer:
\bold{w=(6y-3)/(2)}

Explanation:

Isolate w by performing the following steps

  • Multiply by 6 on both sides to clear the denominator
  • Subtract 3 from both sides
  • Divide both sides by 2


y=(1)/(2)+(w)/(3)\\\\\\6\bigg[y=(1)/(2)+(w)/(3)\bigg]\quad \implies \quad 6y=3+2w\\\\\\6y-3=3-3+2w\quad \implies \quad 6y-3=2w\\\\\\(6y-3)/(2)=(2w)/(2)\quad \implies \quad \large\boxed{(6y-3)/(2)=w}

User Ludesign
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.